Aktivitas Antiproliferatif Ekstrak Terstandar Lengkuas (Alpinia galanga) Berdasarkan Senyawa 1'-Asetoksi Kavikol Asetat Pada Sel Kanker Payudara MCF7 - Sari, Hana Dwi Puspita; , Dr. Muhammad Dai, M.Si., Apt (2017)
Galangal (Alpinia galanga) contains phenylpropanoid as secondary metabolites. 1'-Acetoxy chavicol acetate (ACA) is one of active compound that reported for cytotoxic and antiproliferation activity. This study aimed to determine the cytotoxic and antiproliferative activity 1'-Acetoxy chavicol acetate of the ethanol extract of galangal in breast cancer MCF7 cells. Previous studies have done quantification of 1'-Acetoxy chavicol acetat from pasar Legi, pasar Beringharjo, and pasar Wonogiri. Identification of ACA by TLC with the mobile phase of hexane : ethyl acetate (3: 1). Cytotoxic activity was carried out by MTT method and antiproliferative activity by flow cytometer method with the reagent Propidium Iodide. The results of TLC showed the presence intensity of 1'-Acetoxy chavicol acetate is proportional with the levels of ACA. Cytotoxic activity of galangal extract showed that the higher level of ACA, the higher activity of cytotoxic presented in a lower IC50 value. The ethanol extract of galangal that contained highest levels of ACA (3.798%w/w) has potential cytotoxic against MCF7 with IC50 value 15,8 μg/mL. Antiproliferative activity showed inhibition of cell cycle by cell accumulation at G0-G1 phase.